ALTERATION CORRECTION IN LYMPHOCYTE IMAGE FOR MICRO NUCLEUSES DETECTION - Carni, Domenico Luca; Grimaldi, Domenico; Lamonaca, Francesco (International Journal of Computing, 2014)
The paper presents a method pointed out to detect and to correct the alterations of (i) under-exposure, (ii) overexposure, (iii) out of focus, (iv) Gaussian noise, affecting the images acquired into the flow cytometer. These alterations reduce the image quality and interfere with the correct micro nucleus detection in lymphocyte. The objective of the proposed correction is to make the image able to be correctly processed by the pattern matching algorithm (i) to detect the micronucleus into human lymphocytes, (ii) to minimize the doubtful detections, and (iii) to enhance the confidence that in the rejected images are not including the micro nucleuses. The results of numerical tests confirm the validity of the proposed correction method.